Properties of the Complete Phonon Spectrum of Anisotropic One- and Three-layer Wurtzite Nanostructures - Ju.O. Seti; M.V. Tkach (Журнал нано- та електронної фізики)
Within the Loudon dielectric continuum model, the theory of phonon spectrum is developed for the anisotropic wurtzite nanostructures: plane one-layer with binary and ternary components and three-layer with the same components. The energy spectra of confined, interface, semi-interface and propagating phonons are calculated and analyzed. It is shown that the specific properties of phonon spectrum of three-layer nanostructure are the result of proper superposition of phonon spectra of binary and ternary component subsystem.